An investigation of fluid transport in porous solids using nuclear magnetic resonance - Holmes, William Matthew (2001)
A commercially available NMR spectrometer has been used to investigate fluid transport within porous solids. Two water-wet porous solids were investigated. The first was a sample of Fontainebleau sandstone, and the second was an idealised porous solid made from a random packing of glass beads. The samples were saturated with two immiscible phases, i.e. an oil and water phase. Pulsed field gradient (PFG) NMR measurements of one- and two-dimensional displacement probability distributions are reported, for steady-state flow and diffusion, within two phase saturated porous solids. Measurements were made with the porous solids prepare in different steady-state saturations. NMR relaxation measurements are also reported. Using the NMR data it was possible to evaluate the physical importance of parameters such as wettability and phase saturation on transport phenomena in two phase saturated porous solids. Various computer simulations were developed to model the experimental data.